PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, DAN TINGKAT SUKU BUNGA TERHADAP NILAI PERUSAHAAN PADA SUB SEKTOR PULP AND PAPER YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ernalko "; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to examine partially and simultaneously the influence of investment decisions, funding decisions and interest rates on firm value. Where the independent variables in this study are investment decisions, funding decisions and interest rates while the dependent variable is the value of the company. The sample used is secondary data derived from the company's financial statements in the pulp and paper sub-sector listed on the Indonesia Stock Exchange The sampling method uses purposive sampling. The sample used is as many as 6 companies. The data analysis technique used is simple linear regression and multiple linear regression. The results of the study partially show that investment decisions, funding decisions and interest rates do not affect the value of the company. While simultaneous investment decisions, funding decisions and the level of interest there is no influence on the value of the company.Keywords: investment decisions, funding decisions, interest rates and firm value